Leader-Member Exchange, Job Embeddedness, dan Turnover Intention: Peran Islamic Work Ethics - Hanuna Shafariah; Hendryadi Hendryadi (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2021)
This paper aims to investigate the roles of Islamic work ethics (IWE) as moderators of the relationship between leader-member exchange (LMX) with job embeddedness and turnover intention, and the mediating effect of job embeddedness on LMX and turnover intention relationship. Data were collected from 162 employees from twelve private organizations in Indonesia through a self‐report questionnaire. The hypotheses were tested and analyzed using confirmatory factor analysis and mediation-moderation was estimates using the PROCESS macro. The results reveal the positive relationship between LMX and job embeddedness, negative relationship LMX and turnover intention, and also job embeddedness and turnover intention. IWE negatively moderate the direct and indirect eﬀects of LMX on turnover intention through job embeddedness, but positively moderates the LMX - job embeddedness relationship. Theoretical and practical implications, limitations, and directions for future research are offered